Lives of great monks and nuns - Li, Rongxi; Dalia, Albert A. (BDK English Tripiṭaka, 2002)
The life of Aśvaghos̥a Bodhisattva / translated from the Chinese of Kumārajīva by Li Rongxi -- The life of Nāgārjuna Bodhisattva / translated from the Chinese of Kumārajīva by Li Rongxi -- Biography of Dharma Master Vasubandhu / translated from the Chinese of Paramārtha by Albert A. Dalia -- Biographies of Budhist nuns / translated from the Chinese of Baochang by Li Rongxi -- The journey of the eminent monk Faxian / translated from the Chinese of Faxian by Li Rongxi